PERANCANGAN ANIMASI BERKENDARA YANG AMAN DAN NYAMAN - Astriana Mulyani; Dimas Armanda (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
The high rate of motorcycle accidents, especially in adolescents is increasing, which at that age adolescents tend to neglect the factor of safety of himself and others. Disciplinary problems in the use of safe driving (safety riding) bad traffic is a phenomenon that occurs in large cities in developing countries. To the knowledge of safe driving, known as Safety riding a provision which must be held before the start of driving on the road. The difficulty of finding material about proper riding safety for teens make teenagers difficult to understand the contents of the content material on safety driving. Based on these problems, the authors create an interactive animated educational program to facilitate teenagers riding safety in understanding how to drive safe and comfortable which is expected to develop discipline in driving especially among teenagers.